Analisis Kebutuhan Berprestasi dalam Publikasi Artikel Ilmiah Mahasiswa: Studi Komunitas ATLAS FUSHPI UIN Raden Fatah Palembang - Fikra, Hidayatul; Vera, Susanti; Fitriani, Fitriani; Darmalaksana, Wahyudin (Jurnal Perspektif, 2024)
This research aims to analyze the need for achievement in achieving the publication of students' scientific articles. This research uses a qualitative approach by applying the case study method to the Academic Writing Class community at the Faculty of Ushuluddin and Islamic Thought, Raden Fatah State Islamic University, Palembang. The formal object of this research is based on David C. McClelland's need for achievement theory which seeks to analyze the material object of achievement in the publication of scientific articles for students in the Academic Writing Class community. The results and discussion of the research show that the Academic Writing Class community has the drive to exceed, achieve standards, and strive hard to succeed according to aspects of David C. McClelland's need for achievement theory in achieving the publication of students' scientific articles. The research conclused that the Academic Writing Class community has fulfilled aspects of the need for achievement in the form of superior publication of student scientific articles at the Faculty of Ushuluddin and Islamic Thought, Raden Fatah State Islamic University, Palembang.